A Comparative Study of Energy Sector's Variability of Countries in the Organization of Turkic States - Ibrahim Niftiyev; Elshan Bagirzadeh (Book of proceedings: 6th International Congress on Economics, Finance & Energy “Economic Resilience for Sustainable and Inclusive Growth in the Multi-Crises Era”, Istanbul Türkiye October 24-26, 2024, 2024)
The energy sector is critical to economic growth and development, and the everchanging world order requires a new review of past and current trends in this area. This paper focuses on the members of the Organization of Turkic States (OTS) that share a common history, similar cultural and political perspectives, and similar national interests. While some OTS countries are net exporters of electricity energy (e.g., Azerbaijan, Kazakhstan, and Turkmenistan), others are net importers of it (e.g., Türkiye, and Hungary), and cooperation among member and observer states is growing rapidly. This paper documents the similarities and differences in energy sector variability among OTS members using a principal component analysis (PCA) of data between 1991 and 2021. Our study shows that all OTS countries are similar in terms of primary energy consumption per capita, but in terms of electricity consumption and renewable electricity per capita, Hungary and Kyrgyzstan differ from the rest of the sample. Additionally, carbon intensity varies to the same extent in Hungary, Kyrgyzstan, Turkmenistan, and Türkiye. Finally, Hungary and Kyrgyzstan have not changed their fossil fuel-based electricity generation, while Azerbaijan, Kazakhstan, and Turkmenistan show the same positive trend in electricity energy trade. The results of this study provide an integrated and methodological overview of the energy sector of the OTS countries and shed light on possible future cooperation between the member and observer countries.
Additional information: Conference langing page: http://2024.efecongress.org/
Keywords: 330; Dimension Reduction; Energy Sector; Energy Economics; Energy Transition; Organization of Turkic States (OTS); Principal Component Analysis (PCA)